2017
DOI: 10.1093/rheumatology/kew465
|View full text |Cite
|
Sign up to set email alerts
|

Clinical associations with venous thromboembolism in anti-neutrophil cytoplasm antibody-associated vasculitides

Abstract: Our results highlight a role of CRP, baseline creatinine, and cutaneous and gastrointestinal involvement in the risk stratification as being associated with thromboembolic events. Moreover, there might be an association between VTEs and subsequent development of malignancy and disease activity in general.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
32
3
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(48 citation statements)
references
References 22 publications
10
32
3
3
Order By: Relevance
“…Moreover, we identified a trend toward an association between VTE and disease activity. A recent analysis of 417 patients from several randomized trials demonstrated an association between higher disease activity and VTE events , reinforcing the role of active vasculitis in predisposing individuals to thrombosis.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Moreover, we identified a trend toward an association between VTE and disease activity. A recent analysis of 417 patients from several randomized trials demonstrated an association between higher disease activity and VTE events , reinforcing the role of active vasculitis in predisposing individuals to thrombosis.…”
Section: Discussionmentioning
confidence: 85%
“…Analysis of a large cohort of patients with eosinophilic granulomatosis with polyangiitis (EGPA), GPA, and MPA demonstrated occurrence of VTE in 8.2%, 8.0%, and 7.8% of patients, respectively . More recently, analysis of data derived from several trials conducted by the European Vasculitis Society showed the occurrence of VTE in 41 (9.8%) of 417 patients with GPA or MPA . While VTE is now acknowledged as a commonly occurring complication of AAV, its pathogenesis remains ill‐defined.…”
Section: Introductionmentioning
confidence: 99%
“…Schließlich haben Patienten mit aktiver Vaskulitis ein deutlich erhöhtes Thromboserisiko (8-10 %) [52,53], sodass bei langer Hospitalisierung und bei geringem Blutungsrisiko an eine prophylaktische Antikoagulation jedenfalls gedacht werden sollte. Während der initialen Phase der Erkrankung (hohe Steroiddosis, additive Immunsuppression und Aktivität der Grunderkrankung) ist eine antibiotische Prophylaxe mit Trimethoprim-Sulfamethoxazol sinnvoll [24,54].…”
Section: Erhaltungstherapie -Was Wird Empfohlen?unclassified
“…A large retrospective cohort study of AAV subtypes found VTE incidences of 8.2% among patients with eosinophilic granulomatosis with polyangiitis (EGPA), 8% among patients with GPA, and 7.6% among patients with microscopic polyangiitis (MPA) (5). A recent study of trial data from the European Vasculitis Study group found c-reactive protein (CRP), cutaneous involvement, gastrointestinal involvement, and worsening renal function to be associated with increased risk of VTE among patients with GPA and MPA (6). Patients with AAV also have a greater risk of cardiovascular events, such as acute coronary syndrome, new onset angina, peripheral vascular disease, and transient ischemic attacks, which can be seen in patients with prothrombotic states (7).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have sought to uncover molecular determinants of active vasculitis. There is increased recognition that antibodies against proteinase-3 (PR3) correlates well with the incidence of VTE (6,8). A slightly older study, however did note a protective effect of PR3 ANCA (1).…”
Section: Introductionmentioning
confidence: 99%